Problematika Izin Membuka Tanah Negara (IMTN) sebagai Dasar Penguasaan Tanah di Samarinda - Amsari Damanik (Jurnal Hukum Lex Generalis, 2021)
There are several ways to obtain land that can be done through two ways, namely; 1) "Originair" or the acquisition of rights is dwarfed by government determination, be it in the form of conversion or registration of land for the first time. The position of the land can be obtained through the application of rights; 2) Derivatives or land obtained through certain legal acts such as buying and selling, grants, inheritance, auctions, or investment. Especially in Samarinda City, with the birth of Samarinda City Regional Regulation No. 2 of 2019 on Permits to Open Land in the Country resulted in state land in Samarinda City becoming the basis of mastery of state land. However, land allocation with the label Of State Land Clearing Permit (IMTN) is prone to misuse of its designation. Basically, IMTN is only a basis for the use of state land to realize legal certainty and as a follow-up to the improvement of land certification. The object of IMTN itself is not intended in the framework of land commercialization. IMTN in Samarinda which is the implementation of Law No. 23 of 2014 on Local Government has been contained in Samarinda City Regional Regulation No. 2 of 2019 and Samarinda City Mayor Regulation No. 61 of 2019. In the provisions of the local regulations, there is a prohibition to transfer land with IMTN that can have an impact on the buying and selling deeds carried out. The efforts of the parties, both local governments and stakeholder stakeholders, and the community are shoulders to shoulder so that there is no horizontal conflict.